Factors associated with inadequate prenatal care service utilization in Ethiopia according to the WHO recommended standard guidelines - Woldeamanuel, Berhanu Teshome (Frontiers in Public Health, 2022)
Background Adequate maternal health care could prevent 54% of maternal deaths in low- and middle-income countries. In Ethiopia, the maternal mortality rate was reduced from 817 to 412 deaths per 100,000 live births between 2000 and 2016. Thus, the current study focuses on the adequacy of prenatal care (PNC) services rather than the mere prenatal contacts available to assess compliance with the WHO recommended standard guidelines. Methods A nationally representative cross-sectional dataset from the Ethiopian Mini Demographic and Health Survey 2019 was analyzed. Risk factors for prenatal care adequacy were assessed using a multilevel ordinal logistic regression model. Results About 43% of women met the old WHO recommendation of at least four prenatal contacts, while only 3.5% of women met the new WHO recommended minimum of eight prenatal contacts. The overall adequacy of prenatal care based on the four prenatal care utilization indicators was 52.1% no PNC, 37.4% received inadequate PNC and 10.5% received adequate PNC. Being a rural resident [AOR = 0.694 (95% CI: 0.557, 0.865)] and wanting no more children [AOR = 0.687 (95% CI: 0.544, 0.868)] are associated with inadequate prenatal care. Higher educational attainment of women and spouses, exposure to the media, upper wealth quintile, and a perceived shorter distance to a health facility were significantly associated with adequate prenatal care. Conclusion The prevalence of adequate prenatal care was lower. Multi-sectoral efforts are needed to improve maternal health targets by reducing maternal mortality through improved health care services.